The Existence of Nedosa Customary Offence in the Sangihe Community Related to the Development and Renewal of the National Criminal Law - Michael Barama; J. Ronald Mawuntu; Caecilia J. J. Waha; Jemmy Sondakh (Journal of The Community Development in Asia, 2022)
The purpose of this research is to conduct an analysis and study related to how the existence of the Nedosa offense as a Sangihe customary crime and how this offense is included in the renewal of the national criminal law. The prohibition of Nedosa is still existed nowadays and is obeyed by the community and traditional leaders, the settlement is still using customary law methods even though the judicial system has been implemented by the general court. By using a normative juridical research method that focuses on the study of documents and legal materials, both laws and customary decisions are found to be (1) Judiciary, using Law No. 1 Drt/1951 concerning Provisional Measures to Organize Unitary Powers and Procedures for Civil Courts. (2) The case of Donor or â€œBlood Pollutionâ€ (Delik Nedosa) is a unique crime that only exists in the Sangihe Talaud Customary Rules. Both 1917 and 1932 customary rules as well as the 1951 declaration stated that marriage is forbidden between people whose families are in a straight line up and down, cousins, and siblings. The maximum penalty is 5 years in prison. Therefore, the role of the Nedosa offense is very important in the customary law which is still respected and obeyed by the Sangihe Talaud community today. Nedosa's offense is wider than Zinah in the Criminal Code because this offense is related toÂ religion and the perpetrator will be thrown into the sea.